Economic Growth and Oil Industry Development: Assessment of the Interaction of National Economy Indicators - Saad MLAABDAL; Olena CHYGRYN; Aleksy KWILINSKI; Oleksandr MUZYCHUK; Oleksandr AKIMOV (Communications of International Proceedings, 2020)
The results of the national economy functioning determined by the huge complex of factors: structure of the national economic complex, the share of leading industries, the effectiveness of their development and the impact on socio-economic indicators of the country and regions of oil extraction complex. The purpose of the paper is to investigate the scientific approaches to the impact of oil price fluctuations on the economic growth of exporting countries and assessing the interaction of economic growth of the national economy and factors of the oil industry. To study the cointegration and causal relationships of the development of national economy the paper proposed a two-tier approach: on the basis of the heterogeneous modified OLS (FMOLS) model, a linear relationship is established between the indicators of economic development (GDP, capital and labor costs) and indicators of the functioning of the national economy (volumes of oil production and rent payments for oil); the causal links between the economic growth of national economy, the volume of oil production and rent payments are determined by the Granger method based on the developed time series model (VECM), which allows you to adjust the short-term dynamics of parameters depending on the identified long-term relationships between variables and their deviations. The results of the study of cointegration and causal links between the development of the oil industry and the national economy showed that the growth of oil production and the level of rent payments for oil increase GDP for OPEC countries, high and middle-income countries. For countries with low and below average income levels, a 10% increase in oil production leads to a 0.2% increase in GDP. Insignificant economic benefits for this configuration of countries are associated with the lack of systematic modernization of the industry and necessitate a change in the system of state regulation of exploration and use of oil fields, the transition from extensive to intensive development of oil production complex for high value added products.
Keywords: national economy; assessment; oil production; oil prices; oil rent